Manajemen Sarana dan Prasarana dalam Mendukung Implementasi Kurikulum Merdeka - Hamidah, Leny Wardatul; Khoiruddin, Untung; Purnomo, Nurul Hudha (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2025)
The implementation of Merdeka Curriculum requires the support of adequate facilities and infrastructure and effective management to support contextual, flexible learning, and encourage student independence. However, there are still challenges such as limited facilities, non-optimal management, and less than optimal utilization. This study aims to examine the management of facilities and infrastructure at Al Huda Junior High School Kediri Town, including planning, procurement, arrangement, utilization, and elimination, in order to determine the school's readiness in supporting the implementation of the Merdeka Curriculum. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation from the principal, vice principal of facilities, vice principal of curriculum, P5 teachers, and students. Data analysis was carried out through data reduction, validity checking, and conclusion drawing using the triangulation method. The results showed that the management of facilities and infrastructure has been implemented systematically. Planning is done through meetings, analysis of the Education Report Card, and preparation of priority needs. Procurement is outlined in the School Activity and Budget Plan (RKAS) through purchases, grants, repairs and self-making with official documentation. Arrangements include inventory, storage and routine maintenance. Utilization is optimized through usage schedules, Standard Operating Procedure (SOP), training, and integration in project-based learning. Removal has not been done yet, but procedures have been prepared if needed.